Spherical Micro/Nano Hierarchical Structures for Energy and Water Harvesting Devices (Small Methods 7/2022). Issue 7 (20th July 2022) - Jung, Young; Ahn, Junseong; Kim, Ji‐Seok; Ha, Ji‐Hwan; Shim, Jaehwan; Cho, Hanchul; Oh, Yong Suk; Yoon, Yong‐Jin; Nam, Youngsuk; Oh, Il‐Kwon; Jeong, Jun‐Ho; Park, Inkyu
Abstract : Inside Front Cover In article number 2200248, Jeong, Park, and coworkers developed a new strategy for generating spherical micro/nano hierarchical structures (S‐HS) by combining the nanopatterned structures and expandable microspheres. These S‐HS, which enable the control of nanopatterns and the density of spherical microstructures, dramatically increase the surface area and roughness. Effective electrical energy and water harvesting devices are demonstrated through the fabricated hierarchical structures.